PERAN SOSIAL MEDIA DALAM PENYEBARAN MISINFORMASI TENTANG VAKSINASI COVID19 - Diego Yenmis; Elva Ronaning Roem; Rinaldi . (Jurnal Ranah Komunikasi, 2022)
The spread of Covid19 in Indonesia has entered a severe phase so people are asked to be extra careful when doing activities wherever they are. The Indonesian government is coordinating with the World Health Organization (WHO) to carry out vaccination efforts for all people to prevent further spread of this virus. However, it seems that the hard efforts made by the Government are not fully proportional to the enthusiasm of the news on social media lately. The rise of hoaxes circulating has created misinformation about Covid-19 so that the focus of the community is divided. This research is dialysis using a multi-layered model of risk definition in the context of the Covid19 pandemic by Krause et al. This research uses descriptive qualitative method with constructivist paradigm. Data collection techniques used are interviews, observation and documentation. While the data analysis technique used is the Miles and Huberman technique.